2011
DOI: 10.1111/j.1600-0609.2011.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐engraftment syndrome after unrelated donor umbilical cord blood transplantation in patients with hematologic malignancies

Abstract: Pre-engraftment syndrome (PES) after umbilical cord blood transplantation (CBT) remains poorly characterized, and the prognosis and appropriate management are unclear. Therefore, we retrospectively analyzed the incidence, risk factors, manifestations, and clinical outcomes of PES in CBT recipients, who had been treated for hematologic malignancies at our transplantation center. PES was defined as unexplained fever higher than 38.3°C that is not associated with documented infection and unresponsive to antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
(52 reference statements)
2
25
1
Order By: Relevance
“…[8][9][10][11] Although the pathogenesis was poorly understood, pre-ES could have developed long before neutrophil engraftment, of which the cumulative incidence was generally higher than that of ES, due to less stringent diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Although the pathogenesis was poorly understood, pre-ES could have developed long before neutrophil engraftment, of which the cumulative incidence was generally higher than that of ES, due to less stringent diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Furthermore, pre-engraftment syndrome (pre-ES), which is more emphasized with a fever, rash and an occurrence in the pre-engraftment period, has been described and considered different from ES. [8][9][10][11] We retrospectively analyzed the clinical records of 176 patients following allogeneic HSCT. Furthermore, in a comparative study of the clinical features of pre-ES and ES patients, we found that both clinical syndromes were similar, which could be defined as a new entity of a clinical syndrome, termed as peri-engraftment syndrome (peri-ES).…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] PES is reported after conventional and RIC transplants. Data are conflicting as to whether acute GVHD incidence is increased in persons with prior PES and whether PES influences NRM and survival.…”
Section: Pre-es (Pes) After Umbilical Cord Blood Transplantationmentioning
confidence: 99%
“…[7] Another study identified patients with PES as being at risk for both acute and chronic GVHD. [8] The use of cyclosporine for GVHD prophylaxis has been established as a risk factor for PES,[9] while the use of methotrexate for acute GVHD prophylaxis has been shown to reduce the incidence of early immune reactions after UCBT.…”
Section: Introductionmentioning
confidence: 99%